STUDI FENOMENOLOGIS TERHADAP PERILAKU MEROKOK PADA REMAJA PEREMPUAN USIA SMP DI KABUPATEN OGAN ILIR - Hervina Nathasya (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This study discusses the phenomenon of smoking among adolescent girls, which is increasing and becoming a global concern. This study aims to identify factors that encourage smoking behavior among adolescent girls, including the influence of the social and psychological environment. The method used is qualitative with a phenomenological approach, involving semi-structured interviews with junior high school students in Ogan Ilir. The results of the study indicate that the influence of the friendship environment, pressure received from the social environment, and the urge to be considered by the group play an active role in the smoking behavior of adolescent girls. In addition, internal factors such as emotions and the desire to overcome stress also play a role in this smoking behavior. This study is expected to provide insight into designing more effective interventions in preventing smoking among adolescent girls and increasing public awareness of the dangers of smoking.